The importance of education on disasters and emergencies: A review article - Sogand Torani; Parisa Moradi Majd; Shahnam Sedigh Maroufi; Mohsen Dowlati; Rahim Ali Sheikhi (Wolters Kluwer Medknow Publications, 2019)
Disasters and emergencies have been increasing all over the world. Todays, with technological advancement, acquiring knowledge and its application in the realm of action is regarded as the only effective way for prevent disasters or reducing its effects. The present study aimed to review the importance of education and the effect of different methods of education on disaster risk reduction and preparedness in vulnerable people. To this aim, some articles indexed in Database of PubMed, Web of Science, Google Scholar, Scopus, Science Direct, and ProQuest were searched. The search was limited to reviewed articles in English published between 1990 and 2017. In addition, the selected articles were reviewed for relevant citations. The conducted studies were reviewed by two researchers independently. The primary search generated 128 relevant references. After eliminating the duplicates and articles which were not related to the review of the abstract, 41 references were identified for inclusion. After reviewing more, 31 references, which failed to meet inclusion index, were excluded from the study. Disaster education aims to provide knowledge among individuals and groups to take actions to reduce their vulnerability to disasters. During the last decades, the issue that trained people can be prepared for disasters and responding well has been extensively investigated. Based on the results, disaster education is a functional, operational, and cost-effective tool for risk management. Based on some evidence, it is important for vulnerable people to learn about disasters. There are different methods to educate vulnerable people, but no method is better than others. Trained people can better protect themselves and others. In this regard, planning and designing comprehensive educational programs are necessary for people to face disasters.